RECONDITIONING TECHNOLOGY DIRECTLY INTO OPEN PIT MINING OF SOME TECHNOLOGICAL EQUIPMENT SUBASSEMBLIES - Alexandru, Florea Vlad (International Multidisciplinary Scientific GeoConference SGEM, 2018)
The rocks exploited in quarries have certain physical, mechanical and technological characteristics that favors the intense wear, especially by abrasion of the active surfaces of the subassemblies of the technological equipment. Some spare parts and subassemblies are subject to similar wear phenomena, as is the case with the excavators bucket teeth in the lignite pits and the loaders cup teeth in the basalt pits. In the case of the basalt aggregates which are the main raw material needed for the development of the roadways their manufacturing technology takes place in several stages, according to the quality requirements prescribed by the technical norms of construction, namely: extraction of massive rock, crushing, granulation, sorting and loading of aggregates. The production of aggregates from quarries in Romania is carried out with some equipment such as excavators, the crushers has processed rock and loaders for the resulting materials and deposit it in stock or load them in tracks for delivery to the beneficiary. In the paper are presented the results of the researches effected for finding the reconditioning technology applied directly in the quarry to the subassemblies of the equipment in order to reduce the production costs.